At the heart of women in management research: Theoretical and methodological approaches and their biases - Fagenson, Ellen A. (Journal of business ethics, 1990)
This paper examines the dominant theoretical approaches in the field of women in management (WIM) that have been applied to explain women's limited ability to assume organizational positions of significant power. The propositions of traditional (gender-centered and organization structure perspectives) and a newer theoretical perspective (gender-organization-system approach) are discussed. It is proposed that the theories embraced by WIM researchers bias the factors they examine, the methodologies they employ, the statistical techniques they apply, the results they obtain and the conclusions they reach. This is shown to be a particular problem with the gender-centered and organization structure perspectives and not the gender-organization-system approach.